Blahosklonný komunikační styl - Zeman, Jiří (Stylistyka, 2021)
This contribution deals with the role of stereotypes in interaction with older adults. It concentrates on the patronizing speech and its reflection in the structure of conversation. This speech is identified by the presence of clarification and simplification strategies.